DRIVING CUSTOMER LOYALTY: THE ROLES OF SERVICE QUALITY, TRUST, AND SATISFACTION IN XYZ E-COMMERCE - Tandri, Wilbert Tandri; Genoveva (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2025)
The rapid development of the digital economy in Indonesia has had a positive impact on the national economy. XYZ e-commerce is an e-Commerce that provides interactive buying and selling between sellers and buyers online in the form of a mobile application to make it easier for users to carry out online shopping activities without having to open the website via a computer device. The population in this research are people who shop online through XYZ e-commerce and belong to generation Z. The purpose of this research is to determine the influence of service quality, customer trust, and customer satisfaction on customer loyalty at XYZ e-commerce. This research was conducted using questionnaires distributed via Google Form and completed using Structural Equation Model (SEM) and Smart PLS 4.0 version with a total of 259 respondents. The type of population used in this research is an unlimited population and the sampling technique uses purposive sampling. The findings showed a direct relationship between variables used in this study. There is a positive and significant influence between service quality and customer satisfaction. Apart from that, customer trust has a positive and significant influence on customer satisfaction. Customer satisfaction also has a positive influence on customer loyalty. Meanwhile, service quality has a positive and significant influence on customer loyalty. Customer trust also has a positive and significant influence on customer loyalty